Design for multiplicity: a proposal for the integration of different areas with mutual contributions (Research, Society and Development, 2022)
This article presents the proposal of the research group “Design for multiplicity (Design+)”. This aims to investigate design connections with other areas of knowledge, integrating academia and society through the social contributions made possible through these links. Initially, the group investigates the connections between design and the areas of health and law, being able to integrate other areas according to the demands of project development. The grouped surveys bring together projects in the lines of information design in education and health, intellectual property and innovation, in addition to multidisciplinary projects and processes. It uses in its methodology, of a theoretical, exploratory and qualitative nature, technical procedures of case study and bibliographical survey when presenting references related to the case of a specific research group. This article presents by results a discussion about the main themes and actions of each line of research, with authors who support the discussion. In the final considerations, there are statements about the integration of such areas and their relevance for design research.